2019
DOI: 10.3389/feduc.2019.00035
|View full text |Cite
|
Sign up to set email alerts
|

Structural Factors and Policy Change as Related to the Quality of Early Childhood Education and Care for 3–4 Year Olds in the UK

Abstract: In many developed countries it is now the norm for preschool children to spend time outside the home in early childhood education and care (ECEC). Research indicates that attending ECEC can promote longer-term positive life outcomes, which is more likely when the ECEC is of higher quality. In a UK study of 600 ECEC group settings for 3-4 year olds, staff qualifications were predictive of quality at private (for profit) settings. For voluntary (not for profit) settings, which were more homogenous in staff quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Defining quality in this specific setting is not a straightforward process, given the complexity of the concept and the unique met the developmental needs of this age group. As Melhuish & Gardiner (2019) found, while state-funded nurseries had less favorable ratios, they still showed higher process quality compared to private programs, most likely due to higher caregiver qualifications (Melhuish & Gardiner, 2019;Goelman et al, 2008) stated that teacher education is a "major predictor of children's developmental outcomes" (p. 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining quality in this specific setting is not a straightforward process, given the complexity of the concept and the unique met the developmental needs of this age group. As Melhuish & Gardiner (2019) found, while state-funded nurseries had less favorable ratios, they still showed higher process quality compared to private programs, most likely due to higher caregiver qualifications (Melhuish & Gardiner, 2019;Goelman et al, 2008) stated that teacher education is a "major predictor of children's developmental outcomes" (p. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Wages and working conditions included elements such as, staff turnover (n = 4), wages (n = 9), working conditions (n = 2), and sufficient staffing (n = 2). Higher staff/educator wages and lower turnover are common features of highquality programming (Jenkins, 2003;Melhuish & Gardiner, 2018;Minervino, 2014;Saluja et al, 2001). Two sources also indicated that turnover can have a negative effect on children and argued that programs in public school systems may be able to ensure lower turnover rates.…”
Section: Wages and Working Conditionsmentioning
confidence: 99%
“…Literature supports that effective policy modi cations can increase program quality along with program impact (Melhuish et al, 2019). Structural characteristics are therefore the distal and regulable aspects of ECE and thus the main objective of statutory quality regulations.…”
Section: Assessing Program Quality Contributes To Policy Development and Increases Policy Impactmentioning
confidence: 99%
“…This situation means that in those countries early childhood educators are not as well qualified or as well paid as teachers who work with older children, making it more difficult to recruit and retain the high quality early childhood educators all young children deserve. Indeed, low investment in early childhood educators' qualifications, professional development, working conditions and pay is not only disrespectful of educators and the young children they work with, but it is also poor policymaking because it disregards robust evidence that well trained, well qualified early childhood educators raise the quality of provision and improve young children's lifetime outcomes (European Commission Directorate-General for Education and Culture 2014; Melhuish and Gardiner 2019).…”
Section: Respect For Early Childhood Education: Editorialmentioning
confidence: 99%